Cilician Survey - Seton-Williams, M. Y.
Geographical Description — Topographical and Literary Sources — The Country — Prehistory of the Area — The Survey: The Coastal Strip on the Gulf of Iskenderun; The Çukur Ova and the Aleïan Plain — The Date of the Mounds: Chalcolithic Sites; Early Bronze Age; Middle Bronze Age; Imperial Hittite Period; Iron Age; Persian Period; Hellenistic and Roman Periods — Conclusions — Catalogue of Sites in the Cilician Plain.